Historical Narratives and Myths in the Adzan Pitu Tradition: Representations of Local Islamic Civilization at the Sang Cipta Rasa Grand Mosque - Hudaini, Mumtasya; Khotimah, Husnul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The Adzan Pitu tradition at the Sang Cipta Rasa Grand Mosque in Cirebon is a religious practice that serves not only as a ritual but also as a meeting point between history, belief, and the construction of meaning within the local Muslim community. This tradition is worth studying because it presents a variety of evolving narratives, some rooted in the historiography of Islam’s spread in Cirebon and others emerging as collective myths within the community. Building on this, this study aims to trace how the origin narratives of the Adzan Pitu are constructed across various literary sources and how the tradition is represented and maintained within the framework of local Islamic civilization. This study employs a qualitative approach through a literature review, examining books, scholarly articles, and writings related to the history of Islam in Cirebon and the religious traditions of the Indonesian archipelago. The data obtained were analyzed using a descriptive-interpretive approach, with an emphasis on how narratives are constructed, conveyed, and interpreted within a sociocultural context. The findings indicate that the narrative regarding Adzan Pitu does not stand as a single, unified version but is composed of various layers of stories that blend historical and mythological elements. In its development, the continuity of this tradition is supported not only by historical legitimacy but also by the power of the narrative, which is continuously reproduced through the social and religious practices of the community. Thus, Adzan Pitu can be understood as a representation of a living local Islamic civilization, where language, stories, and symbols play a crucial role in maintaining the continuity of the tradition.